2021
DOI: 10.3390/ma14102540
|View full text |Cite
|
Sign up to set email alerts
|

On Growth and Morphology of TiO2 Nanotubes on Ti6Al4V by Anodic Oxidation in Ethylene Glycol Electrolyte: Influence of Microstructure and Anodization Parameters

Abstract: Different studies demonstrated the possibility to produce TiO2 nanotubes (TNTs) on Ti6Al4V alloy by electrochemical anodization. However, the anodizing behavior of α and β-phases in organic electrolytes is not yet clarified. This study reports on the anodizing behavior of the two phases in an ethylene glycol electrolyte using different applied potentials and anodizing times. Atomic force and scanning electron microscopies were used to highlight the anodic oxides differences in morphology. It was demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…10 However, this effect has not been reported in organic media/fluorine-based electrolytes because in organic media the aggressive nature of − F ions reduces, which influences the dissolution rate. 21 Similarly, fluorine-based electrolytes are important to form such nanostructures as hydrochloric acid-based electrolytes with similar acidity cannot produce TiO 2 nanostructures at 60 V. 1 In our work, the length of the nanorods and nanowires is in the range of 500-700 nm. This is in good agreement with the previously reported studies.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…10 However, this effect has not been reported in organic media/fluorine-based electrolytes because in organic media the aggressive nature of − F ions reduces, which influences the dissolution rate. 21 Similarly, fluorine-based electrolytes are important to form such nanostructures as hydrochloric acid-based electrolytes with similar acidity cannot produce TiO 2 nanostructures at 60 V. 1 In our work, the length of the nanorods and nanowires is in the range of 500-700 nm. This is in good agreement with the previously reported studies.…”
Section: Resultsmentioning
confidence: 59%
“…1 The nanostructures on Ti64 were formed at 20 V and 25 V, but not at 15 V. It has been reported that at 10 V, a nanoporous oxide film is formed; at 20-40 V, TiO 2 nanotubes are formed, whereas, at 50 V, a sponge-like porous structure is formed on Ti64 in ammonium sulfate and ammonium fluoride electrolytes. 5,7,21,24 Figures 2b and 2c, show the morphological analysis of nanorods and nanowires at 20 V and 25 V, respectively. In the literature, the formation of such nanostructures on Ti64 by anodization has not been reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations